Don't know, don't care or confused: what do Australian adolescents know about Australian Dietary Guidelines?. Issue 2 (4th May 2018) - Farringdon, Fiona; Hands, Beth; Chivers, Paola
ABSTRACT: Western Australian adolescents are not adhering to the Australian Dietary Guidelines yet little research has considered what adolescents know about the Healthy Living Pyramid (HLP), the recommended daily serves. Four studies assessed nutrition-related knowledge or influences on food preference. Studies one and two investigated adolescent's perceptions of healthy and unhealthy food and what influences their food choice by conducting 24 gender-specific focus groups ( n = 150, 12–16 years). Study three ( n = 28, 13–14 year) assessed the test–retest reliability of a nutrition questionnaire that measured knowledge of the HLP and the recommended daily serves. Study four ( n = 38, 12–16 years) measured changes in HLP knowledge after a six session community-based cooking and food-literacy program. Participant's knowledge about discretionary foods and vegetables was high, however, knowledge about intake of the other food groups especially grains was poor. Body image emerged as the strongest influence over food preference with media reinforcing girl's desire to be thin and boy's desire to be muscular.